THE DEVELOPMENTAL OF WORKSHEET BASED ON SCIENTIFIC APPROACH ON THE TOPIC RECYCLING CARBON OF BIOGECHEMICAL CYCLE FOR TRAINING SCIENCE PROCESS SKILLS TO STUDENTS OF GRADE X - Tutut Ningrum; Widowati Budijastuti (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2019)
Worksheets based on scientific approach are one of the learning tools used to train science process skills for students of biogeochemical cycle material on the carbon cycle. This research aims to produce a valid, effective, and practical worksheet. This research method used a research development with 4D development model which aredefine, design, develop, and disseminate, but the stage disseminate are not done. Limited trials are done to 20 students at SMAN 1 Kedungpring, Lamongan in January-February 2019, the measured parameter is the degree of validity in terms of feasibility aspects which are content, presentation, language, the conformity withthe scientific approach and the suitability of the worksheet for practicing the process skills. For the level of practicality is reviewed by the implementation of students activities and responses while the level of effectiveness is reviewed in terms of the result of the analysis of indicators and the post-test score. The data collected by the validation method to determine the validity, methods of observation for student activities and student questionnaire to determine the level of practicality, the test method to determine the effectiveness of data analysis using a quantitative descriptive method. The data gives the result that the validity of worksheet obtaining a score of validity of 4 that are included in the category of very valid, effectiveness level of 85% which is entered in the category of very effective, and the level of practicality is very good and very practical to obtain a percentage of 92% of student activity on worksheet 1, 96.87% of student activity on worksheet 2 and 96% in terms response of students. It was concluded, worksheet based scientificapproach can practice the process skills because feasibility aspects whice are valid, practical and effectively in learning. Keywords: Student Worksheet development, Scientific Approach, Recycling Carbon.